Solid-phase synthesis of oligoribonucleotides using 9-fluorenylmethoxycarbonyl (Fmoc) for 5'-hydroxyl protection. - Lehmann, C (1989)
Efficient solid-phase synthesis of a series of oligoribonucleotides of up to 20 residues is described that utilises the 9-fluorenylmethoxycarbonyl group (Fmoc) for 5'-protection and 4-methoxytetrahydropyran-4-yl (Mthp) for 2'-protection of ribonucleotide monomers and a phosphoramidite coupling procedure. The Fmoc group is removed after each coupling step by treatment with 0.1M DBU in acetonitrile. Oligoribonucleotides are isolated in 2'-protected form in good yield and shown to be readily and efficiently deprotected by mild acidic treatment.